Determination of nut properties and chemical compositions of walnut (Juglans Regia L.) genotypes grown in walnut-fruit forests of Kyrgyzstan - (:unkn) unknown (Parlar Scientific Publications, 2020)
In this study, sixteen genotypes selected from walnut-fruit forests in the Osh and Jalal-Abad regions of Kyrgyzstan evaluated for nut properties and chemical composition. The nut traits such as nut dimension, nut and kernel weight, kernel ratio, and shell thickness were investigated. The ash, protein, oil, carbohydrate content and fatty acid composition of genotypes were also evaluated. The ranges of average nut characteristics determined for the selected genotypes were: 27.4-32.1 mm nut length; 23.8-28.6 mm nut width; 24.1-29.0 mm nut suture; 7.15-13.17 g nut weight; 3.26-5.65 g kernel weight; 35.02-46.15% kernel percentage and 1.13-2.23 mm shell thickness. The oil content of the genotypes ranged from 55.47 to 65.26%, the protein content ranged from 16.59 to 19.97%, and the carbohydrate content was between 14.02% and 22.85%. The ash content ranged from 1.67 to 2.23%, and the moisture content of the kernels was between 2.06 and 2.58%. The oleic acid content of the oils ranged from 18.62 to 32.19%. The linoleic acid content ranged from 46.13 to 62.25%, while linolenic acid content ranged from 6.67 to 13.05%. The palmitic acid content was between 4.98 and 7.67%. Sary-Chelek 1, Arslanbap 3, Arslanbap 4 and Kara-Alma 3 genotypes were identified as the promising genotypes according to nut characteristics and chemical composition. © 2020 Parlar Scientific Publications. All rights reserved.
Keywords: Fatty acids; Kyrgyzstan; Nut traits; Walnut